A dexterous motion control method of rope driven snake manipulator considering the rope-hole properties. (May 2023) - Gu, Haiyu; Gao, Haibo; Wei, Cheng; Huang, Zhuoran
Abstract: The RDSM (rope driven snake manipulator) is a hyper redundant robot operating in narrow and confined space. However, the rope-hole properties of the mechanism are ignored mostly, resulting in the significant trajectory tracking error of the RDSM. To solve the problem, a RDSM prototype with 16 DOFs is designed firstly. Then the rope-hole nonlinear model is established considering the friction, clearance and rope flexibility. Based on the rope-hole nonlinear model, the rope length is corrected, and the kinematic model of the RDSM without considering the rope-hole properties is improved. The joint state observer and trajectory tracking controller of the RDSM are designed using the improved kinematic model. Finally, the proposed kinematic model and controller of the RDSM are verified by the virtual prototype and experimental prototype. The results show that the control precision of the RDSM can be improved significantly with the rope-hole compensation. The end position error is improved from the level of cm to mm, and the end attitude error is improved by about 60%. Highlights: Rope-hole properties cause the rope length error of rope-driven snake manipulators. Rope-hole properties include the friction, clearance and rope flexibility. Rope-hole nonlinear model can correct the kinematic model of rope-driven mechanisms. Rope-hole compensation reduces the posture error of the rope-driven snake manipulator.